Habituation Internalization of Religious Moderation Values in Early Childhood in Pasraman: A Case Study on Pasraman Samiaga Mataram - Wiguna, Ida Bagus Alit Arta; Widyasari, Ida Ayu Putri Genta (Kumarottama: Jurnal Pendidikan Anak Usia Dini, 2025)
Religious moderation is a crucial principle in the pluralistic national education system, especially in the context of Hindu non-formal religious education in Indonesia. This study aims to analyze the habituation process of internalizing religious moderation values in early childhood in Pasraman Samiaga Mataram, as well as identify the learning strategies used by Acarya in shaping students' moderate character. The approach used is a qualitative case study with data collection techniques through observation, in-depth interviews, and documentation. The hypothesis of this study states that the more intensive and contextual the habituation process is carried out, the higher the level of internalization of the value of moderation in early childhood. The results of the study show that learning activities such as Dharma Tula, Yoga, and Dharma Yatra are effectively a medium for habituation of the values of tolerance, peace-loving, and non-violent attitudes, even though students do not understand the concept of moderation terminologically. Affective and contextual strategies have been shown to be more effective in shaping moderate behavior than expository approaches. This article contributes to the development of a theory of Hindu character education based on religious moderation at an early age by emphasizing the importance of a habitual learning approach in instilling abstract values. These findings reinforce the urgency of updating pasraman pedagogy and relevance in shaping an inclusive and adaptive young generation during social diversity. The findings of this study are key to creating a non-formal education model that effectively addresses the challenges of diversity and potential intolerance starting from an early age.